Application of Active Debate Methods in Improving Student Learning Outcomes - Wa Mira La Hasu; Citra Ratifa La Apu (Indo-MathEdu Intellectuals Journal, 2020)
This research is backgrounded because of the lack of mathematics teachers in applying learning methods that are in accordance with the characteristics of students and the material to be taught so that it affects the quality of learning and learning outcomes in the classroom. This study aims to determine the application of active methods of debate in improving student learning outcomes. The type of research used is class action research which consists of four stages, namely action planning, action implementation, obervation and reflection with a total of 26 subjects. Data collection techniques are observation and tests. Observation is carried out to observe learning activities. The test is used to determine student learning outcomes after participating in learning activities with the application of the active method of debate. The results of data analysis on learning outcomes, before the action was 11.53% and after the action was carried out in the first cycle increased to 57.69% and again increased in cycle II, which was 96.15%. The average increase from precyclical to cycle I was 46.16% and from cycle I to cycle II was 49.99%. Meanwhile, the average score obtained by students in the pre-test was 50.09, after action in cycle I increased to 67.69 and again increased in cycle II to 76.92. The average value of the increase from pre-cycle to cycle I was 17.6 and from cycle I to cycle II increased by 9.23.